Challenges and Opportunities for the Market Positioning of “Kintex” SHC in the International Trade in Defense Products - Spassov, Svetoslav (Research Papers, 2024)
The research aims to highlight the contemporary challenges facing the development of the Bulgarian government - owned "Kintex" Share Holding Company, trading in defense production Bulgaria. As such are outlined the poor financial performance in recent years has been outlined, combined with management problems and frequent political changes at the national level, especially against the background of the war in Ukraine and the associated with it increased production and sales by the country's defense industry. At the same time, opportunities are presented that Kintex can take advantage of, and thus the Bulgarian state, which will strengthen the company's image as a trusted partner in the trade of defence products and products with dual use.
Keywords: Kintex; Defense industry; Military expenditures; International trade in defense products